Bibliometric Analysis: Interactive Multimedia For Mathematics Learning - Hilda Kurnia Fitri; Nilah Karnilah; Tuti Hartati; Nurjanah; Asep Simbolon (STAI Miftahul Ula Nganjuk, 2024)
With the development of technology in the 5.0 era, it is possible for students to use technology-based learning media such as interactive multimedia which combines video, animation and audio, thus allowing users to interact and understand the material, as well as increasing learning that is more interesting and interactive. This research aims to see the trend of publication of interactive learning media in mathematics learning from 1993-2023 on Scopus, to see the most countries that study interactive multimedia articles in mathematics learning, to find out published journals regarding interactive multimedia in mathematics learning, and to find out the level of education who use interactive multimedia a lot in mathematics learning. The method used is descriptive research using bibliometrics for publication mapping with the help of VOS viewer. Data collection techniques use Scopus with the keyword’s interactive multimedia and mathematics. The amount of data retrieved from 359 articles to 38 articles regarding interactive multimedia in learning mathematics. Research results show development publication in 1993-2023 on search sqopus the highest in 2010 was 4 publications with 0.12%. Mathematics education for 29 years has increased every year. Malaysia is the country with the largest number of articles on interactive multimedia, namely 87 articles. The journal that publishes interactive multimedia articles is Educational Technology and Society with 79 articles. Writer article the highest of each is article written by (Goodwin, 2008). The level of education that often uses interactive multimedia is Junior High School (SMP) with 10 articles.